Computational Study on Optoelectronic Property Tuning of Oligothiophenes via Chemical Modifications for Solar Cell Applications - Franco, Francisco C. (Asian Journal of Chemistry, 2017)
Chemical modifications in conjugated polymers offers the possibility of tuning its optoelectronic properties for various applications. In this report, the optoelectronic properties of chemically modified oligomers based on poly(3-hexylthiophene-2,5-diyl) (P3HT) were investigated via DFT and TDDFT. The study was carried out by replacing the hydrogen in the 3’-position of the bithiophene monomer unit with several substituents. The polymer properties were predicted via oligomer approach where n, was varied from 1 to 10. Various electronic and optical properties were calculated: EHOMO, ELUMO, EGap, first singlet excitation energy (EOpt) and exciton binding energy (EB). Several substituents: -CN and -F were observed to have significantly lower EHOMO/ELUMO values while having similar EGap compared to P3HT. Relevant solar cell characteristics were predicted and show that P3HT-CN and P3HT-F have significantly improved open-circuit voltage (VOC). The results suggest that P3HT-CN and P3HT-F may have overall better solar cell characteristics than P3HT.